Microgrants as a pathway for community development: A case study exploring impacts, implementation and context. (4th May 2023) - Chivers, Claire; Crabbe, Christine; Fullforth, Jan; Groome, Jeremy; Hoadley, Jenny; Jensen, Anne; Beardmore, Amy; Jones, Mat
ABSTRACT: Microgrant schemes are used in many contexts relevant to community development, but there are few detailed accounts of their operation and effects. This study explored a four-year microgrant scheme in Bristol, UK. The research analyzed 141 awards and collected qualitative and quantitative data on 233 individuals. The research found that the diversity of activities, local embeddedness, skills and capacity development, social connection and volunteering features of the scheme offered routes to community development goals. Microgrant schemes are likely to benefit from designated staff to conduct outreach work, facilitate stakeholder engagement, and provide ongoing support. Coordination with other community development activities enhanced the scheme's impact while weaknesses in local infrastructure, caused by funding cuts, impeded delivery. Microgrant schemes should be understood as an intervention that complements and works alongside other community development activities. To enhance their role in community development, attention needs to be paid to scheme design, implementation and integration.